Arc Flash Analysis based on IEEE 1584-2018 and NFPA70E-2018 - et. al., Dr. M.Gopila, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Arc flash is the dangerous hazard, with possible release of energy caused by an electric arc which can cause damage to the equipment and personal. The purpose of the IEEE 1584 and NFPA 70Es is to calculate the energy level and help to achieve the appropriate protection to the working personals. Using IEEE 1584-2018 and NFPA 70E 2018, we can achieves more accurate calculations and Personal Protective Equipments recommendations compared with IEEE 1584 -2002 and NFPA 70E -2002 with the parameters Open circuit voltage, electrode configuration, bolted fault current, gap width, arc flash duration working distance and enclosure size.